2012
DOI: 10.1159/000339695
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Initial Disease Recurrence after Resection of Biliary Tract Cancer

Abstract: Objectives: This study aimed to provide further insights into the indications for adjuvant therapeutic strategies via analysis of the sites of initial recurrence after resection of gallbladder cancer (GBC) and intrahepatic (IHC) and extrahepatic cholangiocarcinoma (EHC). Methods: Patients with biliary tract cancer who underwent potentially curative resection were identified from the database. Sites of initial disease recurrence were categorized as locoregional or distant. Results: Between March 2001 and April … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 60 publications
1
39
0
Order By: Relevance
“…Moreover, the majority of patients who undergo curative resection experience tumor recurrence or metastasis [5]. Therefore, systemic chemotherapy has become a mainstay of treatment for most patients with BTC [6,7].…”
Section: Introductionmentioning
confidence: 48%
“…Moreover, the majority of patients who undergo curative resection experience tumor recurrence or metastasis [5]. Therefore, systemic chemotherapy has become a mainstay of treatment for most patients with BTC [6,7].…”
Section: Introductionmentioning
confidence: 48%
“…Park and colleagues showed that more than 60% of patients with resected extrahepatic biliary cancer had llocoregional recurrence (22). Jung and coworkers reported even higher locoregional recurrence rates, of 70%, 86%, and 57%, in patients with gallbladder, intrahepatic, and extrahepatic cancer, respectively (23). Several retrospective studies have shown that chemoradiation can improve local control and overall survival in selected patients in both adjuvant and neoadjuvant settings (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…One meta-analysis revealed that chemotherapy or chemoradiotherapy had a statistically greater benefit than radiotherapy alone (32). It has also been reported that remote organ metastasis is more frequently observed than locoregional recurrence of biliary carcinoma after surgery (28)(29)(30)(31). Therefore, adjuvant treatment with systemic chemotherapy might have some advantage in the regulation of recurrences after drastic local treatment such as surgery as compared with local radiotherapy.…”
Section: Discussionmentioning
confidence: 99%